Pengaruh Pemberian Infused Water dengan Kombinasi Jahe Merah, Stroberi, dan Daun Mint terhadap Daya Tahan Aerobik pada Atlet Sekolah Bola Basket - Ana Yuliah Rahmawati; Dwi Nanda Mutiarani; Arintina Rahayuni (Poltekkes Kemenkes Semarang, 2025)
Background: Basketball is a high-intensity and fast-paced sport, often leading athletes to experience fatigue before the game concludes. Players' performance in basketball is supported by good aerobic endurance, which constitutes approximately 65% of the game's physical demands. Infused water containing red ginger, strawberries, and mint leaves is rich in antioxidants. Antioxidants help neutralize free radicals, thereby maintaining the athletes' aerobic endurance.Objective: To determine the difference in aerobic endurance before and after the administration of infused water with red ginger, strawberries, and mint leaves in basketball school athletes.Method: This study employed a pre-experimental design with a one-group pre-test and post-test approach, involving a single group measured for aerobic endurance before and after receiving the infused water. The infused water was administered six times over two weeks during each training session. The sample consisted of all members of the U-18 team, totaling 28 athletes, selected through total sampling. Data analysis was conducted using the Paired T-test.Results: The study found that the infused water containing red ginger, strawberries, and mint leaves exhibited an antioxidant activity of 89%, categorized as very strong. Following the two-week intervention, there was a significant difference in the aerobic endurance values of the basketball athletes before and after consuming the infused water, with a p-value of 0.005.Conclusion: Infused water with red ginger, strawberries, and mint leaves can serve as a natural sports drink alternative, as it effectively enhances aerobic endurance in basketball athletes.